Strategic Development of Tamang Island Tourism towards a Tourism Village: An Islamic Economic Perspective Based on Al-Ghazali’s Principles - Amin Akbar; Marliyah Marliyah; Aqwa Naser Daulay (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
The purpose of this study is to identify effective strategies for developing Tamang Island into a tourism village, framed within the Islamic economic perspective of Imam al-Ghazali. The research employs a qualitative descriptive method, using field research, observations, interviews, and documentation for data collection. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is utilized to assess internal and external factors influencing development. The results indicate that Tamang Island's position, based on the IFAS and EFAS matrices, is in Quadrant II, recommending a WO strategy to address internal weaknesses by leveraging external opportunities. Specific strategies include: (1) improving deteriorated tourist attractions, (2) enhancing coordination between government, managers, and investors to secure development funding, (3) rejuvenating neglected infrastructure, (4) utilizing tourism activities to stimulate local economic growth and create employment, (5) leveraging supportive policies from the Mandailing Regency Government, such as tourism training and promotion, and (6) establishing a cooperative or village-owned enterprise (BUMDes) to manage Tamang Island's tourism operations. From an Islamic economic perspective, the findings align with Imam al-Ghazali’s principles of maslahah (public benefit), adl (justice), and iktisad (moderation). The development strategies prioritize economic sustainability, equitable resource distribution, and community empowerment, while safeguarding environmental integrity and fostering ethical tourism. The study concludes that integrating al-Ghazali's economic principles into tourism development enhances not only economic outcomes but also aligns with broader Islamic values, contributing to sustainable and ethical tourism practices